704 OBSERVATIONAL MEDICAL TREATMENT OR SURGERY FOR GIANT PARAOESOPHAGEAL HIATAL HERNIA IN ELDERLY PATIENTS. (17th September 2021) - Braghetto, Italo; Korn, Owen; Lanzarini, Enrique; Musleh, Maher; Figueroa, Manuel; Rojas, Jorge
Abstract:  : Giant paraoesophageal hernias (GPHH) occur frequently in the elderly, account for about 5–10% of all hiatal hernias. Up to now persists the controversy between expectant medical treatment versus surgical treatment, regarding which is the most appropriate option depending on the presence or absence of symptoms. The aim of this study is to assess whether an indication for surgical repair of PHH is possible in older patients adequately evaluated before surgerymptoms. Methods: Patients and method: Prospective study including patients hospitalized from January 2015 to December 2019 with GPHH more than 70 years old, comparing 2 group of patients which were separated in: Group A including a cohort of 23 patient in whom observational and conservative was indicated by gastroenterologist and Group B includes 66 patients in whom elective laparoscopic hiatal hernia repair was indicated at the moment of its diagnosis. Results: Charlson's score and ASA II or III were more frequent in group A. Emergency hospitalization was exclusively seen in group A and elective surgery in Group B. Symptomatic patients were seen in both groups (86.9 and 86.4% respectively). Symptoms period before the hospitalization was more prolonged in group A (21.8 + 7.8 vs 6.2 + 3.5 years) (p = 0.001). Symptoms of acute complications were seen frequently in Group A UCI and hospital stay were significantly more prolonged in Group A due to sepsis, emergency surgery and complications. In hospital mortality occurred in 5/23 patients (21.7%) in group A vs 1/66 patients (1.5%), Group B. Conclusion: 1 Symptomatic patients were observed in both groups 2 Severe complication and mortality were significantly higher in group A. 3 Once the diagnosis of hiatal hernia is confirmed, patients must be operated electively after a multidisciplinary preoperative evaluation to avoid disastrous outcome